2008
DOI: 10.1172/jci35114
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of transcription factor early growth response 1 reduces herpes simplex virus lethality in mice

Abstract: Herpes simplex virus type 1 (HSV-1) infection is the most common cause of sporadic, fatal encephalitis, but current understanding of how the virus interacts with cellular factors to regulate disease progression is limited. Here, we show that HSV-1 infection induced the expression of the cellular transcription factor early growth response 1 (Egr-1) in a human neuronal cell line. Egr-1 increased viral replication by activating promoters of viral productive cycle genes through binding to its corresponding sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
(48 reference statements)
4
26
0
Order By: Relevance
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 52%
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 52%
“…We also showed that Egr-1 could activate the promoter of the HSV-1 gene, infected cell protein 4 (ICP4), which has recently been reported to activate the VEGF-A promoter (10,44). The induced FGF-2 and VEGF-A can, in turn, augment Egr-1 expression (27,35).…”
mentioning
confidence: 79%
“…Additionally, HSV-1 infection may increase Egr-1 expression indirectly through cellular factors. We previously revealed that the 5= end of the Egr-1 promoter containing a cyclic AMP (cAMP) response element and binding sites for several transcription factors, including SP1, AP1, and Egr-1 itself, was required for HSV infection to increase Egr-1 expression (1,10). HSV infection increases the expression or the activities of cAMP, SP1, and AP1 (6,18,21) and may enhance Egr-1 expression in infected cells through these mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vero cells were maintained and propagated according to the instructions of the American Type Culture Collection. Wild-type HSV-1 strains 294.1 (15)(16)(17)(18) and McKrae (kindly provided by Donald Coen, Harvard Medical School) were propagated and titrated on Vero cell monolayers. All mouse experiment protocols were approved by the Laboratory Animal Committee of National Cheng Kung University.…”
Section: Methodsmentioning
confidence: 99%